TINGKAT KEPATUHAN PEMILIK USAHA KOS ATAS PEMAHAMAN PAJAK KOS DI KECAMATAN PARONGPONG - Jhonaen Sinaga; Marthinus Ismail (Jurnal Ekonomis, 2023)
The need for temporary houses that are used as facilities for workers and students who live around industrial sites and universities is a profitable business opportunity for boarding business owners. Therefore, this study aims to determine the understanding of boarding business owners about the Tax Law, how to calculate and how to report compliance with paying cost tax. Using primary data through questionnaires. The study population is domiciled in Parongpong District, especially Cihanjuang Rahayu Village and Karya Wangi Village. Sampling through convenient sampling and found 28 respondents and processed with analysis of description, correlation, determination, and significance after a normality test. The results of the study found that the relationship between understanding the Tax Law was strong (r = 0.69) with WP compliance, with a contribution of 48% and a significant effect (sig. 0.00 < 0.05). The relationship between understanding how to calculate is strong (r = 0.74) with WP compliance, with a contribution of 55% and a significant effect (sig. 0.00 > 0.05). The relationship between understanding how to report is very strong (r = 0.88) with WP compliance, with a contribution of 77% and a significant effect (sig. 0.00 > 0.05). Thus, the level of understanding of taxpayers is a strong factor that causes compliance of taxpayers who own boarding businesses.